Design and study of telomerase inhibitors based on G-quadruplex ligands - Negrutska, V.V.; Dubey, L.V.; Ilchenko, M.M.; Dubey, I.Ya. (Вiopolymers and Cell, 2013)
In this review we have summarized the results of our recent research on telomerase inhibitors and G-quadruplex DNA ligands. A series of potential enzyme inhibitors were synthesized and studied. These compounds were based on tricyclic heteroaromatic systems (thiazolobenzimidazoles phenazines, acridones), amino-substituted cyanines and natural and synthetic porphyrins and their metalocomplexes. A number of compounds, including cyanines and especially porphyrin derivatives and conjugates, were found to efficiently inhibit telomerase at low micromolar concentrations in the in vitro TRAP assay. Porphyrins demonstrated antiproliferative activity in tumor cell cultures at micro- and nanomolar concentrations. Spectral-fluorescent and electrophoretic experiments were performed to investigate the interaction of ligands with duplex and quadruplex DNA, and in many cases binding mode was established. Convenient G-octet model of G-quadruplex was developed to study the ligand-target binding using quantum-chemical methods. QM/MM hybrid approach ONIUM2 was employed to model the interaction of small molecules with Tel22 quadruplex DNA. В огляді підсумувано основні результати наших недавніх досліджень інгібіторів теломерази та лігандів G-квадруплексної ДНК. Синтезовано й вивчено серію потенційних інгібіторів ферменту на основі трициклічних гетероароматичних систем (тіазолобенз- імідазоли, феназини, акридони), амінозаміщених ціанінів та природних і синтетичних порфіринів і їхніх металокомплексів. Знайдено низку сполук – ціанінів та особливо похідних і кон’югатів порфіринів, що ефективно інгібують теломеразу in vitro за умов тесту TRAP у мікромолярних концентраціях. Порфірини у мікро- та наномолярних концентраціях демонструють антипроліферативну дію в культурах пухлинних клітин. Спектрофлуоресцентними та електрофоретичними методами досліджено взаємодію лігандів з дуплексною та квадруплексною ДНК, у багатьох випадках визначено тип зв’язування. Взаємодію ліганд–мішень вивчено методами квантової хімії за використання G-октету як зручної моделі G-квадруплексу. Для моделювання зв’язування малих молекул з квадруплексною ДНК Tel22 застосовано гібридний QM/MM- підхід ONIOM2. В обзоре суммированы основные результаты наших недавних исследований ингибиторов теломеразы и лигандов G-квадруплексной ДНК. Синтезирована и изучена серия потенциальных ингибиторов фермента на основе трициклических гетероароматических систем (тиазолобензимидазолы, феназины, акридоны), амино-за- мещенных цианинов, природных и синтетических порфиринов и их металлокомплексов. Обнаружен ряд соединений – цианинов и особенно производных и конъюгатов порфиринов, эффективно ингибирующих теломеразу in vitro в условиях теста TRAP в микромолярных концентрациях. Порфирины в микро- и наномолярных концентрациях демонстрируют антипролиферативное действие в культурах опухолевых клеток. Спектрофлуоресцентными и электрофоретическими методами исследовано взаимодействие лигандов с дуплексной и квадруплексной ДНК, во многих случаях определен тип связывания. Взаимодействие лиганд–мишень изучено методами квантовой химии с использованием G-октета как удобной модели G-квадруплекса. Для моделирования связывания малых молекул с квадруплексной ДНК Tel22 применен гибридный QM/MM-подход ONIOM2.